Penentuan Umur Simpan Black Sesame Body Scrub Powder Dengan Metode Accelerated Shelf Life Testing Model Labuza - Silaen, Thesalonika Racheltauli Putri; Anggreni, Anak Agung Made Dewi; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Shelf life is an important aspect and requirement in the production of a product. Until now, the shelf life of black sesame body scrub powder products is still unknown. This study aims to determine the sorption isotherm characteristics of water and the shelf life of black sesame body scrub powder using the Accelerated Shelf Life Testing Model Labuza method. This research was conducted in two stages, namely analysis of water sorption isotherm characteristics and estimation of shelf life. The results showed that the water sorption isotherm characteristics of black sesame body scrub powder were sigmoid (type II) and the shelf life of the product at 28 o C, 75% humidity, in polyethylene packaging of 0.13 mm thickness, cross-sectional area of 0.064 m2, with a sample weight of 1000 g was 26.21 months or 2.1 years while with polyethylene packaging of 0.13 mm thickness, cross-sectional area of 0.0234 m2, with a sample weight of 100 g was 7.16 months or 0.6 years. Keywords : shelf life, scrub powder, ASLT, Labuza method, Henderson model